A New Glioblastoma Targeting Therapy Concept by Using Square Shaped Janus Drug Carrier Assisted with 3D Printed External Magnetic Wearables. (20th December 2018) - Wei, Chaochao; Liu, Yu; Tian, Xue; Li, Ruolei; Tong, Wanqing; Wang, Shuhua; Xin, Hongbo; Hu, Ping; Wang, Xiaolei
Abstract: At present, the clinical treatment of malignant glioma is still unsatisfactory. The existence of the blood–brain barrier hinders most chemical and biological drugs to reach the brain tissue. In this study, a square‐shaped Janus drug carrying system, which incorporated with high infrared responsiveness, large drug loading capacity, and reliable magnetic targeting capabilities is synthesized. Combined with an external 3D printed magnetic wearable equipment, this carrying system can effectively penetrate the blood–brain barrier in both in vitro and in vivo tests, it is thus applied to two different targeting tumor therapies (including glioma). Animal experiments demonstrate the multiple therapeutic effects of the proposed system. The subsequent studies imply that the obtained carrier has no obvious toxic effects on the organs of animals. Different from the classical biochemical targeting method, this study uniquely combines the porous Janus nanocarrier with an external wearable magnetic guidance device (physical targeting), which is a promising target therapeutic concept with impressive flexibility and reliability. Abstract : A new therapy concept for targeting brain gliomas by combining the square shaped Janus nanocarrier with a 3D printed magnetic helmet is presented. With the aid of external NIR irradiation, the relative animal experiments demonstrated the flexibility and reliability of the proposed system.